Antifungal activity of various essential oils against Saccharomyces cerevisiae depends on disruption of cell membrane integrity - Konuk, Hatice Busra; Erguden, Bengu (Inst Histol Embriol-Conicet, 2017)
Antifungal activity and mode of action of nine essential oils (EOs) against S. cerevisiae cells were examined. Antifungal effects of commercial lemon peel, orange peel, tea tree, turpentine, rosemary, peppermint, thyme, oregano and clove oils were determined through Minimum Inhibitory Concentration (MIC), Minimum Fungicidal Concentration (MFC) and inhibition zone measurements. The most effective oil was turpentine oil. Orange peel, thyme and oregano oils were also effective, according to MIC and MFC. Inhibition zone measurements, also revealed oregano, orange peel, thyme, turpentine and clove oils as most efficient ones. Later, membrane damage of yeast cells was studied by measuring the extracellular pH and conductivity in a concentration dependent manner. Orange peel, turpentine, thyme and oregano oils caused a clear increase in extracellular pH of glucose-induced yeast cells and induced an increase in extracellular conductivity. These results point to the deterioration of yeast cell membrane integrity upon exposure to EOs. Since these oils can be used as food preservatives and pharmaceutical agents, it is very important to understand their mode of action and their main target sites in the cell. Thus this research not only opens new perspectives to understand antifungal activity mechanisms of EOs, but also help widen their use.
Keywords: Saccharomyces cerevisiae; Essential oils; Antifungal activity; Cell membrane